2014
DOI: 10.1007/s00134-014-3337-1
|View full text |Cite
|
Sign up to set email alerts
|

Offering the opportunity for family to be present during cardiopulmonary resuscitation: 1-year assessment

Abstract: At 1 year after the event, psychological benefits persist for those family members offered the possibility to witness the CPR of a relative in cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 28 publications
1
79
0
7
Order By: Relevance
“…The majority were female (21), white (22), postgraduate (24) and worked for more than a year in the emergency unit (23), with professional experience ranging from six months to 15 years (average of 38.5 months of working).…”
Section: Resultsmentioning
confidence: 99%
“…The majority were female (21), white (22), postgraduate (24) and worked for more than a year in the emergency unit (23), with professional experience ranging from six months to 15 years (average of 38.5 months of working).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Therefore, nursing support and implementation of FPDR are vital to the provision of family-centered care. Yet, recent research continues to demonstrate unfavorable or mixed views of FPDR (9) 32 (94) 0 (0) 1 (3) 2 (6) 1 (3) 1 (3) 0 (0) 12 (35) 6 (18) 8 (24) 7 (21) 1 (3) 3 (9) 3 (9) 18 (53) 9 (26) 1 (3) 1 (3) 3 (9) 11 (32) 4 (12) 3 (9) 12 (35) 24 (71) 0 (0) 9 (26) 1 (3) 0 (0) 22 (65) 11 (32) 1 (3) 32 (94) 2 (6) 0 (0) 38 (95) 2 (5) 34 (85) 3 (8) 2 (5) 1 (2) 0 (0) 1 (2) 0 (0) 8 (20) 9 (22) 11 (28) 11 (28) 1 (3) 1 (2) 12 (30) 18 (45) 8 (21) 1 (2) 0 ( www.ajcconline.org among nurses.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…11,12 Demonstrated benefits to family members include maintenance of desired patient-family connectedness and empowerment through being involved in their loved one's care. 5,13 FPDR also facilitates family members' grieving, [14][15][16] which is important because the survival rate for in-hospital cardiac arrest among adults is approximately 18%. 17 Research conducted with nurses and other health care providers has shown that FPDR increases family members' understanding and ability to make care decisions, improves emotional support for families and facilitates their grieving, and promotes professionalism among the members of the health care team.…”
mentioning
confidence: 99%
“…Meeting psychosocial needs in a time of crisis exemplifies care driven by the needs of patients and their families. depression, and traumatic grief are less frequent when families are permitted to be present during resuscitation than when they are not, both at 3 months and at 1 year after the event, with no medicolegal claims 50,56 Actions for Nursing Practice Ensure that your health care facility has written policies and procedures that support family presence during resuscitation and invasive procedures. Create an interdisciplinary task force (ie, nurses, physicians, social workers, pastoral care, respiratory care, child-life specialists, and patient/family advisors) to develop your family presence program.…”
Section: Scope and Impact Of The Problemmentioning
confidence: 99%